How Labor Market Inequality Transforms Mass Politics. Issue 2 (12th April 2020) - Häusermann, Silja; Kemmerling, Achim; Rueda, David
Abstract: Why do left parties lose vote shares in times of economic crisis and hardship? Why do right-wing governments implement seemingly left-wing policies, such as labor market activation? Why is representation becoming more and more unequal? And why do workers vote for right-wing populist parties? Several political science theories propose meaningful and important answers to these key questions for comparative politics, focusing on identity politics, programmatic convergence of parties or exogenous constraints. However, there is an additional and distinct approach to all of the questions above, which emphasizes socio-structural transformations in the labor market: most of the processes above can be understood with reference to increasing labor market inequality and its political implications. The relevance and explanatory power of labor market inequality for mass politics have not been fully acknowledged in comparative political science and this is the reason for this symposium. Labor market inequality affects political preferences and behavior, electoral politics, representation, and government strategies. The main purpose of our symposium is to make broader comparative politics research aware of the crucial structural changes that labor markets have undergone in the advanced capitalist democracies of the OECD, and of the tremendous implications these changes have had for politics.